2010
DOI: 10.1002/jgm.1473
|View full text |Cite
|
Sign up to set email alerts
|

Animal Research: Reporting In Vivo Experiments: The ARRIVE Guidelines

Abstract: ItemRecommendation (Kilkenny et al., 2010) TITLE 1 Provide as accurate and concise a description of the content of the article as possible.ABSTRACT 2 Provide an accurate summary of the background, research objectives, including details of the species or strain of animal used, key methods, principal findings and conclusions of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
1,647
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,674 publications
(1,664 citation statements)
references
References 2 publications
7
1,647
0
10
Order By: Relevance
“…This assumes that the level of current research is inadequate and researchers must improve research study design, data handling, and interpretation. This recommendation is consistent with previous recommendations and publications, including STAIR [20], RIGOR [21][22][23][24] and CAMARADES [25,26], guidelines that are now mainstays in the field. However, based upon manuscript submission to this Journal, there is still less than 30% compliance by research laboratories worldwide primarily because high quality fully transparent research can be costly and there is insufficient funding available (see [30]).…”
Section: Proceedings From the Workhopsupporting
confidence: 88%
“…This assumes that the level of current research is inadequate and researchers must improve research study design, data handling, and interpretation. This recommendation is consistent with previous recommendations and publications, including STAIR [20], RIGOR [21][22][23][24] and CAMARADES [25,26], guidelines that are now mainstays in the field. However, based upon manuscript submission to this Journal, there is still less than 30% compliance by research laboratories worldwide primarily because high quality fully transparent research can be costly and there is insufficient funding available (see [30]).…”
Section: Proceedings From the Workhopsupporting
confidence: 88%
“…All animal care and experimental procedures were conducted in accordance with the National Institutes of Health's Guide for the Care and Use of Laboratory Animals and approved by Wake Forest University's Institutional Animal Care and Use Committee. This study is reported in accordance with the ARRIVE (Animal Research: Reporting of In Vivo Experiments) guidelines for reporting experiments involving animals (60). Twelve adult male and female rhesus monkeys (Macaca mulatta), age 10-17 y and weight 6.5-13 kg, were kept at an indoor facility accredited by the Association for Assessment and Accreditation of Laboratory Animal Care International.…”
Section: Methodsmentioning
confidence: 99%
“…All studies were conducted in accordance with the principles and procedures outlined as "3Rs" in the guidelines of EU (86/609/EEC), FELASA, and the National Centre for the 3Rs (the ARRIVE; Kilkenny et al, 2010), and were approved by the Animal Care Committee of the Center for…”
Section: Subjectsmentioning
confidence: 99%